We think you are located in South Africa. Is this correct?

Finding The Equation

2.5 Finding the equation (EMBFN)

We have seen that the roots are the solutions obtained from solving a quadratic equation. Given the roots, we are also able to work backwards to determine the original quadratic equation.

Worked example 11: Finding an equation when the roots are given

Find an equation with roots \(\text{13}\) and \(-\text{5}\).

Assign a variable and write roots as two equations

\[x = 13 \text{ or } x = -5\]

Use additive inverses to get zero on the right-hand sides \[x - 13 = 0 \text{ or } x + 5 = 0\]

Write down as the product of two factors

\[(x-13)(x+5) = 0\]

Notice that the signs in the brackets are opposite of the given roots.

Expand the brackets

\[x^2 - 8x - 65 = 0\]

Note that if each term in the equation is multiplied by a constant then there could be other possible equations which would have the same roots. For example,

Multiply by \(\text{2}\): \[2x^2 - 16x - 130 = 0\]

Multiply by \(-\text{3}\): \[-3x^2 + 24x + 195 = 0\]

Worked example 12: Finding an equation when the roots are fractions

Find an equation with roots \(-\frac{3}{2}\) and \(\text{4}\).

Assign a variable and write roots as two equations

\[x = 4 \text{ or } x = -\frac{3}{2}\]

Use additive inverses to get zero on the right-hand sides. \[x - 4 = 0 \text{ or } x + \frac{3}{2} = 0\]

Multiply the second equation through by \(\text{2}\) to remove the fraction. \[x - 4 = 0 \text{ or } 2x + 3 = 0\]

Write down as the product of two factors

\[(2x+3)(x-4) = 0\]

Expand the brackets

The quadratic equation is \(2x^2 - 5x - 12 = 0\).

Do you need more Practice?

Siyavula Practice gives you access to unlimited questions with answers that help you learn. Practise anywhere, anytime, and on any device!

Sign up to practise now

Finding the equation

Exercise 2.5

Determine a quadratic equation for a graph that has roots \(\text{3}\) and \(-\text{2}\).

\[x = 3 \text{ or } x = -2\]

Use additive inverses to get zero on the right-hand sides: \[x - 3 = 0 \text{ or } x + 2 = 0\]

Write down as the product of two factors

\[(x - 3)(x + 2) = 0\]

Expand the brackets

\[x^2 - x - 6 = 0\]

Find a quadratic equation for a graph that has \(x\)-intercepts of \((-4;0)\) and \((4;0)\).

The \(x\)-intercepts are the same as the roots of the equation, so:

\[x = -4 \text{ or } x = 4\]

Use additive inverses to get zero on the right-hand sides: \[x + 4 = 0 \text{ or } x - 4 = 0\]

Write down as the product of two factors

\[(x + 4)(x - 4) = 0\]

Expand the brackets

\[x^2 - 16 = 0\]

Determine a quadratic equation of the form \(ax^2 + bx + c = 0\), where \(a, b\) and \(c\) are integers, that has roots \(-\frac{1}{2}\) and \(\text{3}\).

\[x = -\frac{1}{2} \text{ or } x = 3\]

Use additive inverses to get zero on the right-hand sides: \[x + \frac{1}{2} = 0 \text{ or } x - 3 = 0\]

Write down as the product of two factors

\[(2x + 1)(x - 3) = 0\]

Expand the brackets

\[2x^2 - 5x - 3 = 0\]

We note that this solution gives us integer values as required.

Determine the value of \(k\) and the other root of the quadratic equation \(kx^2 - 7x + 4 = 0\) given that one of the roots is \(x=1\).

We use the given root to find \(k\):

\begin{align*} k(1)^{2} - 7(1) + 4 & = 0 \\ k & = 3 \end{align*}

So the equation is:

\(3x^2 - 7x + 4 = 0\)

Now we can find the other root:

\begin{align*} 3x^{2} - 7x + 4 & = 0 \\ (x - 1)(3x - 4) & = 0 \\ x = 1 & \text{ or } x = \frac{3}{4} \end{align*}

One root of the equation \(2x^2 - 3x = p\) is \(2\frac{1}{2}\). Find \(p\) and the other root.

We use the given root to find \(p\):

\begin{align*} 2 \left( \frac{5}{2} \right)^{2} - 3 \left( \frac{5}{2} \right) - p & = 0 \\ \frac{25}{2} - \frac{15}{2} & = p \\ p & = 5 \end{align*}

So the equation is:

\(2x^2 - 3x - 5 = 0\)

Now we can find the other root:

\begin{align*} 2x^{2} - 3x - 5 & = 0 \\ (2x - 5)(x + 1) & = 0 \\ x = 2\frac{1}{2} & \text{ or } x = -1 \end{align*}

Do you need more Practice?

Siyavula Practice gives you access to unlimited questions with answers that help you learn. Practise anywhere, anytime, and on any device!

Sign up to practise now

Mixed exercises

Exercise 2.6

Solve the following quadratic equations by either factorisation, using the quadratic formula or completing the square:

  • Always try to factorise first, then use the formula if the trinomial cannot be factorised.
  • In a test or examination, only use the method of completing the square when specifically asked.
  • Answers can be left in surd or decimal form.

\(24{y}^{2}+61y-8=0\)

\begin{align*} 24y^{2} + 61y - 8 & = 0 \\ (8y - 1)(3y + 8) & = 0 \\ y = \frac{1}{8} & \text{ or } y = -\frac{8}{3} \end{align*}

\(8x^2 + 16x = 42\)

\begin{align*} 8x^{2} + 16x - 42 & = 0 \\ 4x^{2} + 8x - 21 & = 0 \\ (2x - 3)(2x + 7) & = 0 \\ x = \frac{3}{2} & \text{ or } x = -\frac{7}{2} \end{align*}

\(9t^2 = 24t - 12\)

\begin{align*} 9t^{2} - 24t + 12 & = 0 \\ 3t^{2} - 8t + 4 & = 0 \\ (3t - 2)(t - 2) & = 0 \\ t = \frac{2}{3} & \text{ or } t = 2 \end{align*}

\(-5{y}^{2}+0y+5=0\)

\begin{align*} -5y^{2} + 5 & = 0 \\ -5(y^{2} - 1) & = 0 \\ y^{2} -1 & = 0 \\ (y-1)(y+1) & = 0 \\ y = 1 & \text{ or } y = -1 \end{align*}

\(3m^2 + 12 = 15m\)

We will solve this equation by completing the square for practice:

\begin{align*} 3m^{2} + 12 - 15m & = 0 \\ m^{2} - 5m + 4 & = 0 \\ m^{2} - 5m & = -4 \\ m^{2} - 5m + \frac{25}{4} & = -4 + \frac{25}{4} \\ \left(m - \frac{5}{2}\right)^{2} & = \frac{9}{4} \\ m - \frac{5}{2} & = \pm \sqrt{\frac{9}{4}} \\ m & = \frac{5}{2} \pm \frac{3}{2} \\ m = 1 & \text{ or } m = 4 \end{align*}

\(49{y}^{2}+0y-25=0\)

\begin{align*} 49y^{2} - 25 & = 0 \\ (7y - 5)(7y + 5) & = 0 \\ y = \frac{5}{7} & \text{ or } y = -\frac{5}{7} \end{align*}

\(72 = 66w - 12w^2\)

\begin{align*} 12w^{2} - 66w + 72 & = 0 \\ 2w^{2} - 11w + 12 & = 0 \\ (2w - 3)(w - 4) & = 0 \\ w = \frac{3}{2} & \text{ or } w = 4 \end{align*}

\(-40{y}^{2}+58y-12=0\)

\begin{align*} -40y^{2} + 58y - 12 & = 0 \\ 20y^{2} - 29y + 6 & = 0 \\ (5y - 6)(4y - 1) & = 0 \\ y = \frac{6}{5} & \text{ or } y = \frac{1}{4} \end{align*}

\(37n + 72 - 24n^2 = 0\)

\begin{align*} 24n^2 - 37n - 72 & = 0 \\ (3n - 8)(8n + 9) & = 0 \\ n = \frac{8}{3} & \text{ or } n = -\frac{9}{8} \end{align*}

\(6{y}^{2}+7y-24=0\)

\begin{align*} 6{y}^{2}+7y-24 & = 0 \\ (3y + 8)(2y - 3) & = 0 \\ y = -\frac{8}{3} & \text{ or } y = \frac{3}{2} \end{align*}

\(3 = x(2x - 5)\)

\begin{align*} 3 &= 2x^2 - 5x\\ 2x^2 - 5x - 3 &= 0\\ (2x+1)(x-3)&=0\\ x =-\frac{1}{2}& \text{ or } x = 3 \end{align*}

\(-18{y}^{2}-55y-25=0\)

\begin{align*} -18y^2 - 55y - 25 &= 0\\ 18y^2 +55y + 25 &= 0 \\ y &= \dfrac{-55 \pm \sqrt{(55)^2 - (4)(18)(25)}}{2(18)}\\ &= \dfrac{-55 \pm \sqrt{\text{3 025}- \text{1 800}}}{36}\\ &= \dfrac{-55 \pm \sqrt{\text{1 225}}}{36}\\ &= \dfrac{-55 \pm 35}{36}\\ y= -\frac{90}{36} = -\frac{5}{2} &\text{ or } y=-\frac{20}{36} = -\frac{5}{9} \end{align*}

\(-25{y}^{2}+25y-4=0\)

\begin{align*} -25y^2 + 25y - 4 &= 0\\ 25y^2 - 25y+4 &= 0\\ y^2 - y &= -\frac{4}{25}\\ y^2 - y + \frac{1}{4} &= -\frac{4}{25} + \frac{1}{4}\\ \left(y-\frac{1}{2}\right)^2 &= \frac{-16+25}{100}\\ \left(y-\frac{1}{2}\right)^2 &= \frac{9}{100}\\ y-\frac{1}{2} &= \pm \sqrt{\frac{9}{100}}\\ y-\frac{1}{2} &= \pm \frac{3}{10}\\ y = \frac{1}{2}+\frac{3}{10} = \frac{4}{5} &\text{ or } y = \frac{1}{2} - \frac{3}{10} = \frac{1}{5} \end{align*}

\(8(1 - 4g^2) + 24g = 0\)

\begin{align*} -32g^2 + 24g + 8 &= 0\\ 32g^2 - 24g - 8 &= 0\\ 4g^2 - 3g - 1 &= 0\\ (4g + 1)(g-1) &= 0\\ g =-\frac{1}{4} &\text{ or } g=1 \end{align*}

\(9{y}^{2}-13y-10=0\)

\begin{align*} 9y^2 - 13y - 10&= 0\\ y &= \dfrac{-(-13) \pm \sqrt{(-13)^2 -4(9)(-10)}}{2(9)}\\ &= \dfrac{-(-13) \pm \sqrt{169 + 360}}{18}\\ &= \dfrac{13\pm \sqrt{529}}{18}\\ &= \dfrac{13\pm23}{18}\\ y = \dfrac{13+23}{18} = 2 &\text{ or } y = \dfrac{13-23}{18} = -\frac{5}{9} \end{align*}

\((7p - 3)(5p + 1) = 0\)

\begin{align*} (7p-3)(5p+1)&=0\\ p =\frac{3}{7} &\text{ or } p = -\frac{1}{5} \end{align*}

\(-81{y}^{2}-99y-18=0\)

\begin{align*} -81y^2 - 99y - 18 &= 0\\ 9y^2 + 11y +2 &=0\\ (9y+2)(y+1) &= 0\\ y = -\frac{2}{9} &\text{ or } y = -1 \end{align*}

\(14{y}^{2}-81y+81=0\)

\begin{align*} 14y^2 - 81y + 81 &= 0\\ y &= \dfrac{-(-81) \pm \sqrt{(-81)^2 - 4(14)(81)}}{2(14)}\\ &= \dfrac{81 \pm \sqrt{\text{6 561}- \text{4 536}}}{28}\\ &= \dfrac{81 \pm \sqrt{\text{2 025}}}{28}\\ &= \dfrac{81 \pm 45}{28}\\ y = \frac{81+45}{28}=\frac{9}{2} &\text{ or } y = \frac{81-45}{28} = \frac{9}{7} \end{align*}